Verso una città uguale, inclusiva e attiva. L'espressione di giustizia sociale nel concetto di sostenibilità - Francesca Cubeddu (Culture e Studi del Sociale)
Cities are a social construct in which the well-being of subjects is determined by economic capital.The cities are also the expression of social inequality of people who live there. In cities the social and economic condition determines the social status of individuals. If we want to discuss an equal, inclusive and active city, we must define the parameters of a society in which the subjects have the same opportunities and the same possibilities. The concept of social justice is empty if it does not envisage social actions that can guarantee cities an equality and a sustainable social, economic and environmental development.In this context the subject feels recognized as a person and a citizen who participates in social life. This work aims to illustrate with the concepts of social justice and sustainability how cities can achieve the goals supported by the European Union goal for 2030 of making cities not only more sustainable but also inclusive and equal. The first theoretical paragraphs will explain the thesis of the link between social justice and sustainability by analyzing the cities and their development and in the empirical part the verification with some data of such statements.